Technology and equipment for pistol casting - B. A. Kraev; M. A. Sadokha; V. I. Gutko; N. E. Bondarik; A. P. Melnikov (Литьë и металлургия)
Description of main types of pistols, their construction peculiarities and materials used for their manufacture is given. Applied technologies of strengthening of most loaded pistol elements and creation of optimal thermal conditions of their operation are presented.